Gene expression patterns observed from the skin of selected cattle breeds infested with Amblyomma hebraeum ticks - Letuka, Mmanaha (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.